2014
DOI: 10.17557/tjfc.84207
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Quality Responses of Tall Fescue (Festuca arundinacea Schreb.) to Different Irrigation Levels and Nitrogen Rates

Abstract: A 2-year experiment was conducted to investigate the effects of different irrigation levels and nitrogen rates on visual turfgrass colour and quality and clipping yield of tall fescue (Festuca arundinacea Schreb.) under subhumid climatic conditions. The treatments consisted of five levels of irrigation, 25% (I1), 50% (I2), 75% (I3), 100% (I4) and 125% (I5), of the evaporation measured from a Class A pan and two rates of nitrogen, 25 kg N ha -1 (N1) and 50 kg N ha -1 (N2). The N rates were applied as a monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It is important to highlight the positive correlation between turfgrass quality and daily DMP in irrigated turfgrass. Where both variables were recorded in the same study, we observed a positive correlation, with R 2 values for the logistic regression ranging between .60 and .97 (Bañuelos et al., ; Candogan et al., , ; Lee, ; Qian & Engelke, ; Su et al., ; Telenko et al., ; Wherley, ). This nonlinear relationship shows that although low or zero growth rates might compromise turf quality, maximum turf quality scores are achieved before DMP rates reach their maximum.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…It is important to highlight the positive correlation between turfgrass quality and daily DMP in irrigated turfgrass. Where both variables were recorded in the same study, we observed a positive correlation, with R 2 values for the logistic regression ranging between .60 and .97 (Bañuelos et al., ; Candogan et al., , ; Lee, ; Qian & Engelke, ; Su et al., ; Telenko et al., ; Wherley, ). This nonlinear relationship shows that although low or zero growth rates might compromise turf quality, maximum turf quality scores are achieved before DMP rates reach their maximum.…”
Section: Resultsmentioning
confidence: 60%
“…Differences in turfgrass quality among species and varieties became more noticeable as the irrigation amount was reduced. In two studies conducted in Turkey, Candogan, Bilgili, Yazgan, and Acikgoz (, ) reported on the effects of irrigating perennial ryegrass ( Lolium perenne L.) and tall fescue ( Schedonorus arundinaceus [Schreb.] Dumort., nom.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations